Synthetic Analogues of Aminoadamantane as Influenza Viral Inhibitors-In Vitro, In Silico and QSAR Studies - Chayrov, Radoslav; Parisis, Nikolaos A; Chatziathanasiadou, Maria V; Vrontaki, Eleni; Moschovou, Kalliopi; Melagraki, Georgia; Sbirkova-Dimitrova, Hristina; Shivachev, Boris; Schmidtke, Michaela; Mitrev, Yavor; Sticha, Martin; Mavromoustakos, Thomas; et al. (Molecules (Basel, Switzerland), 2020)
A series of nineteen amino acid analogues of amantadine (Amt) and rimantadine (Rim) were synthesized and their antiviral activity was evaluated against influenza virus A (H3N2). Among these analogues, the conjugation of rimantadine with glycine illustrated high antiviral activity combined with low cytotoxicity. Moreover, this compound presented a profoundly high stability after in vitro incubation in human plasma for 24 h. Its thermal stability was established using differential and gravimetric thermal analysis. The crystal structure of glycyl-rimantadine revealed that it crystallizes in the orthorhombic Pbca space group. The structure-activity relationship for this class of compounds was established, with CoMFA (Comparative Molecular Field Analysis) 3D-Quantitative Structure Activity Relationships (3D-QSAR) studies predicting the activities of synthetic molecules. In addition, molecular docking studies were conducted, revealing the structural requirements for the activity of the synthetic molecules.
Keywords: stabilita léku; Madin Darby Canine Kidney Cells; Animals; Antiviral Agents; molecular docking; molekulární konformace; vodíková vazba; Rimantadine; Orthomyxoviridae; Molecular Docking Simulation; buňky MDCK; teplota; vazebná místa; antivirové látky; počítačová simulace; Differential Thermal Analysis; Quantitative Structure-Activity Relationship; 3D-QSAR; amino acids; simulace molekulového dockingu; proteinové domény; lidé; LC–MS/MS.; Drug Stability; plasma stability; Dogs; Molecular Conformation; Protein Domains; krystalografie rentgenová; Least-Squares Analysis; buněčná smrt; metoda nejmenších čtverců; Adamantane; Computer Simulation; Humans; Temperature; Viral Matrix Proteins; rimantadin; X-Ray crystallography; adamantane derivatives; mass spectrometry; diferenční termická analýza; Cell Death; Hydrogen Bonding; adamantan; zvířata; Crystallography, X-Ray; psi; proteiny virové matrix; Binding Sites; kvantitativní vztahy mezi strukturou a aktivitou